A CASE OF ANAL FISTULA TREATED BY INDIVIDUALIZED HOMEOPATHIC MEDICINE - ABHIJIT DUTTA (Innovare Journal of Medical Sciences, 2019)
Objective: Anal fistula is one of the most frequent problems to encounter in clinical practice. In the conventional system of medicine, medication has a minimal role and surgery is the only option. An alternative and gentle treatment plan are always warranted not only for the symptom complex presents in it but also for preventing further complications. Methods: This is the case of a patient presented with pain, offensive discharge and itching near anus for last three months. Afterwards, he was diagnosed as a case of anal fistula based on peculiar history and physical examinations. Treatment was started prospectively following strict homoeopathic principles and follow-ups done in suitable intervals for about four months. Result: A marked improvement was noted gradually in different visits and a marked resolution after the complete the course of the treatment. Discussion: Rationale of the case report is to show the effective management of such cases with proper homoeopathic treatment.